RISET KOMUNIKASI KUALITATIF SEMIOTIKA MAKNA DAN BENTUK PERHITUNGAN WETON PADA TRADISI PERNIKAHAN ADAT JAWA MASYARAKAT DK.GERSAPI, KEC. TUNJUNGAN, JAWA TENGAH - Bambang Haryono; Qoni’ah Nur Wijayani, S.Ikom., M.Ikom (PT. Media Akademik Publisher, 2023)
Javanese customs in the people of Dukuh Gersapi, Tunjungan District, Central Java are a social system that preserves traditional norms. It is known that every wedding in Javanese tradition has several customs that are multifunctional in both the social, spiritual and economic fields. The aim of this research is to examine the semiotic meaning and form of weton calculations in Dukuh Gersapi as a Javanese custom that retains a high level of complexity. This research uses qualitative methods with a semiotic approach to decode the meanings stored in each Javanese wedding custom. The results obtained indicate that this custom allegedly has the aim of ensuring that couples comply with existing customary rules even though some of them cannot be fully understood by people who are not adherents of these Javanese customs. This semiological qualitative communication research provides an overview of the meaning and form of weton calculations in traditional Javanese wedding traditions in Dukuh Gersapi, Tunjungan District, Central Java.